What’s in a Title? Some Remarks on the Semantic Features of Kenning-Like Titles in George R. R. Martin’s A Song of Ice and Fire Series - Neubauer, Łukasz (Studia Anglica Posnaniensia, 2022)
Working on the hugely successful series of novels known collectively as A Song of Ice and Fire, George R. R. Martin is known to have drawn much of his inspiration from real-life events, landmarks in the history of the Middle Ages, such as the Hundred Years’ War, the Wars of the Roses, and the Crusades. It is not known, however, to what degree he actually relies in his work on sources of genuinely medieval provenance, since he himself frequently admits that amongst those that made the biggest impact on his writing are modern works of fiction, such as Maurice Druon’s heptalogy Les Rois maudits (2019 [1955–1977]). It is not impossible, though, that at least some features of Martin’s series have more or less direct parallels in medieval literature. One such element may be so-called kennings, the highly-stylised circumlocutions found in plenty in the poetic works of early Germanic literature and whose diction appears to shine through some of the series’ titles.